FIRST REPORT OF BIO-POLISHING OF JUTE FIBERS USING CELLULASE PURIFIED FROM A NOVEL ISOLATE OF TRICHODERMA LONGIBRACHIATUM IN IRAQ - Noor T. Hamdan; Hameed M. Jasim (Scholar Express Journals, 2021)
The Bio-polishing technique of jute fibers was achieved for the first time in Iraq by using cellulase purified from a novel Iraqi isolate Trichoderma longibrachiatum which recorded first in Iraq in NCBI site as AB1. Enzymatic treatmemt of jute fibers was carried out through the released reducing sugars and percentage of loss in weight of jute fibers were determined , then morphological and structural characteristic were examined by using X-ray diffraction, FT-IR spectroscopy and scanning electron microscope. Enzymatic treatment was achieved by incubating 1200mg of jute fibers with gradual concentrations of purified cellulase enzyme (33, 50 and 100%) for 1-6 hours at 40°C (the optimum temperature of enzyme activity and stability). Results showed that the maximum release of reducing sugars has been achieved after three hours of incubation with the enzyme, where the concentration of released reducing sugars was 1.50, 0.89 and 0.69 mg/ml after the treatment with the enzyme concentrations of 100, 50 and 33% respectively
Keywords: Novel Iraqi isolate; Trichoderma longibrachiatum; Cellulase; Bio-polishing technique